الإعجاز الغيبي في ضوء السنة النبوية ( دراسة موضوعية ) - عروة, مروة (University of Eloued جامعة الوادي, 2017)
عنيت الدراسة ببحث الإعجاز الغيبي في ضوء السنة النبوية، حيث تناولت مفهوم الإعجاز والمعجزة ومفهوم الغيب في اللغة والاصطلاح، ثم مفهوم الإعجاز الغيبي في ضوء السنة النبوية وبعدها تطرقت إلى صلب البحث من خلال دراسة الإعجاز الغيبي في السنة النبوية بأقسامه الثلاثة (الماضي-الحاضر-المستقبل) ، ثم تناولت مسألة الإعجاز الغيبي وعلاقته بالعلم الحديث وشهادات بعض العلماء المعاصرين على صدق نبوة النبي محمد صلى الله عليه وسلم مع ذكر بعض الضوابط والقواعد الضرورية عند تحديد العلاقة بين الإعجاز الغيبي والعلم الحديث , ثم ختمت الدراسة بذكر أهم النتائج التي توصل إليها البحث والتوصيات المقترحة للباحثين والمهتمين بدراسة وبحث جوانب الإعجاز في السنة النبوية. It meant the study to examine the miracle Algbe in the light of the Sunnah, where he dealt with the concept of miracles and the miracle and the concept of the unseen in the language and terminology, then the concept of miracles metaphysical in the light of the Sunnah and then touched to the core of research by studying the miracle of metaphysical in the Sunnah of the three Boqsama (past-present-future ), and then addressed the issue of miracles Algbe and its relationship to modern science and the testimonies of some contemporary scholars of the truth of the prophecy of the Prophet Muhammad peace be upon him with mention some of the controls necessary rules when determining the relationship between the miracle of metaphysical and modern science, and the study concluded by mentioning the most important findings to The research and proposed recommendations for researchers and those interested in the study and research aspects of miracles in the
مذكرة ماستر تخصص علوم الحديث
Keywords: الإعجاز – المعجزة – الغيب – السنة النبوية – أقسام الإعجاز – الإعجاز في القران الكريم; Miracles - Miracles - Unseen - Prophetic Sunnah - Sections of miracles - Miracles in the Koran